Pembinaan Literasi Media Pada Warga Belajar Perempuan PKBM Sumber Ilmu Di Kecamatan Sagulung Kota Batam - Ageng Rara Cindoswari; Muhammad Patli; Hardiyanto Hardiyanto (Prosiding, 2022)
The objectives of this Community Service activity are (1). Knowledge of women learning residents in PKBM Sumber Ilmu about the benefits and uses of the internet, (2). Knowledge of women learning citizens in PKBM Sumber Ilmu about media literacy, (3). Skills for women learning residents at PKBM Sumber Ilmu about preventing the misuse of the internet and social media for misleading news and pornographic content. This activity was held using lecture, discussion and practice methods with a duration of 2 hours per session for 2 meetings. This guidance was given to learning residents of PKBM Sumber Ilmu about 10-15 people which was held in the range of January-February 2018. The results of this activity can be concluded that this coaching is very useful and has an impact on increasing knowledge and improving the way of social life of the community. Media literacy development cannot be done partially and intermittently. This is done so that the target of the media literacy movement can achieve its goals optimally. In addition to fostering media literacy, a theme of community service is needed, such as media literacy parenting. In the implementation of the development of the service team, they did not find significant difficulties because the participants showed high enthusiasm during the training